Gambaran Sanitasi Lingkungan Pada Balita Stunting Usia 24-59 Bulan di Kelurahan Kopo UPT Puskesmas Citarip Wilayah Bojongloa Kaler Tahun 2021 - Manalu, Lisbet Octovia; Indriyani, R.O.; Somantri, Budi (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2022)
Background : Sanitation The environment affects health, including the ownership of healthy latrines and the provision of clean water and waste management. Poor environmental sanitation practices can increase the risk of infectious diseases that can affect nutritional problems in toddlers. In 2020 the number of stunting events in Kopo Village is still high. Objective: This study was to find out how the description of environmental sanitation in stunting toddlers aged 24 - 59 months in Kopo Village UPT Citarip Health Center. Methods: This research uses descriptive quantitative research by collecting data through the distribution of questionnaires given online. The population in this study were parents who had stunting toddlers totaling 167 people. The samples taken in this study were 70 people using stratified random sampling technique. Results: The results of the study on the description of environmental sanitation in stunting toddlers aged 24-59 months in Kopo village with clean and healthy categories as many as 69 people (98.4%) and unsanitary and unhealthy categories as many as 1 person (1.4%). Conclusion: Based on the results of the study, most of the respondents already had good environmental sanitation but their toddlers were stunted, this was because environmental sanitation factors were an indirect cause of stunting and the direct factors that became the risk of stunting were lack of nutritional intake and infectious diseases.